2014
DOI: 10.2224/sbp.2014.42.6.891
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Persuasive Effect of Member-Get-Member Referral Programs

Abstract: Marketers use both financial and nonfinancial incentives to create word-of-mouth (WOM) communication but few empirical researchers have explored how these different types of incentives might affect the design of referral programs and new customer responses to them. In this study we adopted an experimental design and established hypotheses to investigate the persuasive effect of different referral reward programs, such as a member-get-member setup. Our findings show that low-involvement products offer financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Involvement has been shown to be an important driver of organic WOM in a large number of empirical studies (e.g. Neumann, 2015;Wangenheim and Bayón, 2007), and a few studies extended these findings to the RRP context where they showed that high involvement products elicited higher intention to accept incentivized referrals (Chan et al, 2014;Fan et al, 2014). This logic is extended to successful recommendation behavior for the first time in this study.…”
Section: Josm 301supporting
confidence: 67%
See 1 more Smart Citation
“…Involvement has been shown to be an important driver of organic WOM in a large number of empirical studies (e.g. Neumann, 2015;Wangenheim and Bayón, 2007), and a few studies extended these findings to the RRP context where they showed that high involvement products elicited higher intention to accept incentivized referrals (Chan et al, 2014;Fan et al, 2014). This logic is extended to successful recommendation behavior for the first time in this study.…”
Section: Josm 301supporting
confidence: 67%
“…Past studies were largely based on stated intentions with hypothetical RRP scenarios (rather than real RRPs) or self-reported data. Furthermore, an RRP is only effective if inductors recommend and inductees respond with buying the service (cf., Chan et al, 2014;Tuk et al, 2009;Verlegh et al, 2013). As such, it is important to verify findings based on intentions in actual and successful behavior contexts and the present study makes an important contribution to RRP research.…”
Section: Implications For Theorymentioning
confidence: 73%
“…CRV should be distinguished from CIV because of the different motives that customers possess to engage in EWOM behavior. Based on previous studies, self enhancement and economic rewards are the two major concrete motives for customers to contribute value (Chan et al, 2014). Another difference is that CRV is more realized in the acquisition process by bringing new customers, whereas CIV is created more by affecting existing customers to expand purchasing and by encouraging prospects (Kumar et al, 2010).…”
Section: Customer Referral Valuementioning
confidence: 99%
“…In the tourism and hospitality context, the role of CRV has been researched on its influence on customer's purchase intention for travel (Fan et al, 2014). Albeit previous studies have examined the driving factors of referrals from a referrer's perspective (Chan et al, 2014), fewer evidences were found in m-Tourism context. Prior research has further indicated that customers with higher satisfaction levels are more inclined to have higher CLVs and more potential to recommend purchase to other customers (Kumar and Reinartz, 2016).…”
Section: Customer Referral Valuementioning
confidence: 99%
“…Through the assessment of experienced practitioners' feedback of a leading OE institution, the researchers' aim is to display a holistic snapshot of the current RM strategy, steering away from assessing the traditional dyadic consumer-brand relationship focussed on by extant RM literature (Chan et al, 2014;Lee and Anantharaman, 2015;Garnefeld, et al, 2013;Shi and Wojnicki, 2014;Hennig-Thurau et al, 2001). A case study of this magnitude allows the researchers to deduce and propose a conceptual model for an effective RM strategy for the OE sector.…”
Section: Statement Of Purposementioning
confidence: 99%